2017
DOI: 10.31231/osf.io/jxdk8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meditation buffers medical student compassion from the deleterious effects of depression.

Abstract: Increasing data suggest that for medical school students the stress of academic and psychologicaldemands can impair social emotions that are a core aspect of compassion and ultimately physiciancompetence. Few interventions have proven successful for enhancing physician compassion inways that persist in the face of suffering and that enable sustained caretaker well-being. To addressthis issue, the current study was designed to (1) investigate the feasibility of cognitively-basedcompassion training (CBCT) for se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(38 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…One reason for caregiver burnout is the detachment, depersonalization and the erosion of meaning caused in part by repeated exposure to suffering others without tools for handling the accompanying emotional load (Maslach & Leiter, 2016). Our results suggest that CM could be investigated as a technique for maintaining positive emotional connections with patients, potentially reducing burnout (Mascaro et al, 2018) and enhancing patient outcomes (Kaptchuk et al, 2008; Rakel et al, 2011).…”
Section: Discussionmentioning
confidence: 89%
“…One reason for caregiver burnout is the detachment, depersonalization and the erosion of meaning caused in part by repeated exposure to suffering others without tools for handling the accompanying emotional load (Maslach & Leiter, 2016). Our results suggest that CM could be investigated as a technique for maintaining positive emotional connections with patients, potentially reducing burnout (Mascaro et al, 2018) and enhancing patient outcomes (Kaptchuk et al, 2008; Rakel et al, 2011).…”
Section: Discussionmentioning
confidence: 89%
“…There exist a range of interventions/treatments that aim to develop compassion and mindfulness as a critical point in prevention, specifically in medical training. In one important recent study using a specific compassion-based intervention, Cognitively-based Compassion Training (CBCT), Mascaro et al examined its use in second year medical students and showed that there was indeed positive differences in depression, loneliness, sleep, and increased compassion over the course of the intervention in comparison to a wait-list group [1]. Additionally, those students who reported higher levels of depression pre-intervention were noted to receive more benefit in compassion scores than the other students [1].…”
Section: Interventions As Preventionmentioning
confidence: 99%
“…In one important recent study using a specific compassion-based intervention, Cognitively-based Compassion Training (CBCT), Mascaro et al examined its use in second year medical students and showed that there was indeed positive differences in depression, loneliness, sleep, and increased compassion over the course of the intervention in comparison to a wait-list group [1]. Additionally, those students who reported higher levels of depression pre-intervention were noted to receive more benefit in compassion scores than the other students [1]. This shows the possibility that such interventions can assist the majority of students, and may also help in alleviating depressive symptoms and improving compassion in the most vulnerable students.…”
Section: Interventions As Preventionmentioning
confidence: 99%
See 2 more Smart Citations